Marketing Mix Implementation in Small Medium Enterprises: A Study of Galeristorey Online Business - Rora Puspita Sari (ETIKONOMI, 2017)
The purpose of this paper is to evaluate the implementation of marketing mix in online business company, whether the online business adopt solely the traditional marketing mix model or the internet factors is also included, since the business platform itself in on social media. Descriptive research and content analysis using interview and observation were used to analyse the marketing mix implementation in Galeristorey online business. Evidence suggested that Galeristorey implemented few elements of the marketing mix both the traditional marketing mix and the online marketing mix. The cause of the limited use of marketing mix elements because of the barriers faced by Galeristorey as an SME. Further researcher may widen the research sample and creates empirical study on the marketing mix implementation of online business that used social media as its main business platform.DOI: 10.15408/etk.v16i1.3950